Niches and Interspecific Association of Dominant Sciaenidae Species in the Offshore Waters of Southern Zhejiang Province - Yahui YUAN; Shiyu WANG; Chunxia GAO; Jing ZHAO; Qingzhu HUANG (Progress in Fishery Sciences)
Sciaenidae species are economically important in China and contribute to the coastal fisheries industry. They are also key species in many aquatic ecosystems, occupying important food chain and ecosystem positions. However, resources of Sciaenidae species such as Pseudosciaena crocea and Collichthys lucidus have recently declined significantly owing to the combined effects of overfishing, adverse climate change, and marine environmental pollution. Studies on the ecological niche and interspecific relationships of Sciaenidae species are key to understanding their species and population dynamics. Such studies can reveal the ecological positions occupied by Sciaenidae species, their resource utilization, and their interactions, which can serve as a basis for formulating corresponding conservation and management measures. Currently, studies on Sciaenidae species in the offshore waters of southern Zhejiang Province mainly focus on the biological characteristics, age, growth, and feeding of individual fish species; however, a fundamental gap exists in studies on the interspecific relationships of sciaenid fishes. This hinders the conservation and management of these economically important fishery resources. To comprehensively investigate the ecological niche characteristics and interspecific interactions of Sciaenidae species in the offshore waters of southern Zhejiang Province, this study used data from four quarterly fishery resource surveys conducted from May 2020 to January 2021. Ecological niche measurements, cluster analysis, chi-square test, association coefficient, and redundancy analysis were employed to examine the temporal and spatial ecological niche characteristics and interspecific associations of Sciaenidae species in the area. The survey identified nine species of Sciaenidae species, with temporal niche widths ranging from 0.17 to 1.08. Pseudosciaena polyactis had the widest temporal niche width (1.08), followed by C. lucidus at 1.02, whereas Pennahia macrocephalus had the narrowest at 0.17. Spatial niche widths ranged from 1.40 to 2.50, with Atrobucca nibe exhibiting the widest spatial niche width, followed by P. polyactis (2.24), and C. lucidus had the smallest. The spatiotemporal niche widths varied from 0.32 to 2.42, with the P. polyactis exhibiting the largest combined niche width (2.42), which was significantly greater than the other eight species, followed by the Penahia argentata at 1.65. P. macrocephalus had the smallest at 0.32, which was significantly less than the other eight species. These results indicated that P. polyactis had a larger niche width across all three dimensions and was competitively advantageous. In contrast, P. macrocephalus and A. nibe were more affected by the temporal dimension, particularly P. macrocephalus, which was at a competitive disadvantage. Cluster analysis categorized Sciaenidae species into narrow, medium, and wide niche groups based on temporal, spatial, and spatiotemporal. Overall, the niche overlap of this area was low. Regarding time, 30.56% of species pairs had temporal niche overlap above 0.600, 25.00% between 0.300 and 0.600, and 44.44% below 0.300. The highest overlap values were between P. macrocephalus and A. nibe and between Pennahia argentata and Johnius distinctus, both at 0.998, whereas the overlap between the P. macrocephalus and the Miichthys miiuy was the lowest, at only 0.007. In terms of space, most species pairs had low overlap values, with 72.22% below 0.300, 22.22% between 0.300 and 0.600, and only M. miiuy and A. nibe (0.659), as well as P. macrocephalus and P. argentata (0.616), had higher spatial niche overlap values above 0.600. Regarding spatiotemporal, all species pairs had low overlap values, with no pair exceeding 0.600, only 13.89% between 0.300 and 0.600, and the remaining 86.11% below 0.300, indicating that species can coexist through differentiation strategies. The overall association among Sciaenidae species in the area showed a significant positive correlation. The chi-square tests revealed an extremely significant positive correlation only between P. argentata and A. nibe, whereas other species pairs showed non-significant levels of association. Association coefficients indicated that more than half of the species pairs tended to be independent, with only 11.11% showing a high degree of positive association and another 25% exhibiting negative associations. The percentage of co-occurrence indicated that only 8.33% of species pairs had the strongest positive association, whereas the rest (91.67%) had moderate or lower levels of positive association, suggesting that most species pairs distribute independently of each other. This indicates that although a strong overall association exists among Sciaenidae species in the area, implying a certain level of interdependence, the association between species pairs gradually decreases, trending towards an independent distribution pattern. Redundancy analysis results suggest that surface water temperature and salinity are the main environmental factors that affect the distribution of sciaenid fishes in the area, with salinity having the greatest impact.